Permeability profiles and intestinal toxicity assessment of hydrochlorothiazide and its inclusion complex with β-cyclodextrin loaded into chitosan nanoparticles - Onnainty, Renée (2016)
Here, a novel drug delivery system was developed for the hydrochlorothiazide (HCT):β-cyclodextrin (βCD) inclusion complex loaded into chitosan (CS) nanoparticles (NPs) [CS/HCT:βCD NPs]. It was found, for the first time, that exposure of the intestinal mucosa to free HCT resulted in an increased and abnormal intestinal permeability associated with several injuries to the intestinal epithelium. Nevertheless, the HCT delivery system obtained ameliorated the damage of the intestinal epithelium induced by HCT. Furthermore, we found that the corresponding permeability profiles for both the free HCT and the CS/HCT:βCD NPs were exponential and lineal, respectively. We propose that the increased intestinal uptake and severe tissue injury of HCT to the intestinal epithelium could be directly related to possible effects of this drug on the ionoregulatory Na+/K+-ATPase channel. Thus, it is postulated that the CS/HCT:βCD NPs may increase the gastrointestinal retention of the HCT, which would provide increased adherence to the mucus barrier that lines the intestinal epithelium; consequently, this would act as a slow HCT release delivery system and maintain lower drug levels of luminal gut in comparison with the administration of free HCT, leading to less severe local injury.